Effect of phospholipid-protein interfacial interactions on the aeration emulsion quality during reconstitution of fat globule membranes: Interfacial behavior, thermodynamic properties, stability and whipping properties - Guosen Yan; Pan Zhao; Zhenbo Shao; Yiting Li; Jie Han; Yan Li; Liebing Zhang (Food Chemistry: X)
This study examines the interaction between phospholipids (PL) and proteins during the reconstitution of milk fat globule membranes (MFGM) and their effects on structure, properties, and fat crystallization behavior. Adding 0–0.45 % PL altered the MFGM composition, reduced interfacial protein concentration (27.49–37.88 × 10−4 g/m2), interfacial tension (11.05–15.23 mN/m), and droplet sizes (1.53–2.16 μm), while increasing viscosity (20.39–25.11 mPa s), thus enhancing emulsion stability. High PL concentrations caused skin-like folding, increasing interfacial protein content (29.23–29.52 × 10−4 g/m2) and droplet aggregation (1.68–1.71 μm). PL acted as a non-homogeneous nucleating agent, increasing microcrystal formation and nucleation sites but reducing initial crystallization temperature. The reduced mechanical strength of the MFGM decreased cream churning time and overrun, while higher viscosity reduced serum loss and increased hardness. These findings provide insights for improving aerated emulsion quality.